Flexing: Fenomena Perilaku Konsumen dalam Perspektif Islam - Oggy Maulidya Perdana Putri (Jurnal Ilmiah Ekonomi Islam, 2023)
Flexing or show off behavior is one part in the discourse of consumer behavior theory. In 1899, Veblen wrote a book entitled The Theory of Leisure Class which discussed the conspicuous consumption which has similarities to flexing that occurs today. The flexing phenomenon which has recently become an interesting topic of discussion among the society, inseparable from the role of social media which is very influential on people's perceptions and opinions. Moreover, flexing is then associated with fraud and lies. The purpose of this study is to analyze the factors that cause flexing and how this behavior is viewed from the perspective of Islamic consumer behavior theory. The method used is a qualitative research methodology library research with a content analysis approach. The results of this study that there are five factors that cause flexing, namely to increase self-esteem or self-image, getting a spouse from a certain class, as a means of marketing signal, the environment and personality of flexing character and lack of empathy for others. Flexing is also considered not in accordance with the behavior of Islamic consumers because it is contrary to the principles, norms and ethics of consumption and also contrary to the arguments both from the Al Quran and from the hadith of the Prophet Muhammad